The Level of Knowledge and Self-Management is Related to the Quality of Life of Hypertensive Patients - Fitriani, Januarty Nur; Rohmawati, Dhian Luluh; Lukitaningtyas, Dika (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
The level of knowledge, self-management, and self-efficacy is an individual's ability to control blood pressure, perform self-care, and adhere to treatment which in turn can affect a person’s quality of life. The level of knowledge, self-management, and self-efficacy is very necessary for people with hypertension because all three are an important part of determining the quality of life. The study aimed to analyze the relationship between the level of knowledge, self-management, and self-efficacy with the quality of life of hypertension sufferers. This research is a correlation descriptive study using a cross-sectional approach. A purposive sampling technique was used to select 95 respondents as the sample in this study. A knowledge level questionnaire, self-management behavior questionnaire, self-efficacy questionnaire, and WHOQOL-Bref questionnaire were used to collect data. Spearman rank is used for statistical tests. The results showed that the relationship between the level of knowledge and quality of life result was obtained ρ-value 0.005 r= -0.288, the relationship between self-management and quality of life was obtained result ρ-value 0.001 r = 0.330, the relationship between self-efficacy and quality of life obtained result ρ-value 0.095 r=0.172. There is a relationship between the level of knowledge and self-management and quality of life. There is no relationship between self-efficacy and quality of life in hypertension sufferers.